Diseño de un sistema de administración de proyectos en Constructora Villarreal S.A. - Alvarado-Quirós, José David (Instituto Tecnológico de Costa Rica, 2011)
The made work is the “Design of a Management System of projects in Constructora Villarreal S.A.”, who consists in the creation of a system that allows to the company take the control of the projects in which participate and all the related one to them as they are used it, suppliers, contractors, accounts to pay, accounts to receive among others, also a sheet of calculate was created in Microsoft Excel for which it includes: management of the handling of salary lists, another one for the handling of the control of costs and template of verification like mechanism which they assure the development the projects. In order to reach the raised objectives it was made a previous study of all the documentation and information whereupon the company counted and made the control of the projects, in addition diverse meetings with the personnel were made who handles of the company to be related more to the importance data which they were handled for the projects, as well as a brief qualification on software used (PHP, XAMP, and MYSQL) with which this system was designed. Next to the beginning of the programming and design of each one of the modules of the program occurred, as well as the user authentication of itself, the menu of bases and submenus that conform it and giving as a result the creation of the System called Web Database management System - Constructora Villarreal S.A., which allows to make a control of the company by means of the introduction of information which generate the projects daily and with which conceive reports and consultations of all useful information for the company and its employees. Finally calculate sheets for the handling of salary lists, control of costs were created, thus as template of quality verification, security, productivity, atmosphere, among others in the field.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2011.
Keywords: Seguirdad; Proveedores; Contratistas; Control de costos; Control de proyectos